THE USE OF JIGSAW II TO TEACH SPEAKING TO STMIK STUDENTS - Susanti, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract                                                           The purposes of this research are to encourage the students at STMIK Pontianak to                    actively            engage in the classroom discussion and to help the students overcome their speaking problems in reporting the result of discussion. A Classroom Action Research is applied to overcome problems arise in the classroom.Jigsaw II is one type of cooperative learning which is implemented in this study.The technique focuses on students’ interaction in groups, then it may give better achievement of their speaking skill. The observation, documentary study, recording, interview, and field notes become the data collecting technique used.This action research found out that Jigsaw II is effective and useful to teach speaking to the second semester students of STMIK Pontianak, Technique Informatics Program, through improvement of teaching process in the classroom.Keywords : Jigsaw II, Cooperative Learning, Speaking